2006
DOI: 10.1016/j.febslet.2006.04.064
|View full text |Cite
|
Sign up to set email alerts
|

PTEN, a negative regulator of PI3 kinase signalling, alters tau phosphorylation in cells by mechanisms independent of GSK‐3

Abstract: Deregulation of PTEN/Akt signalling has been recently implicated in the pathogenesis of Alzheimer's disease (AD), but the effects on the molecular processes underlying AD pathology have not yet been fully described. Here we report that overexpression of PTEN reduces tau phosphorylation in CHO cells. This effect was abrogated by mutant PTEN constructs with either a catalytically inactive point mutation (C124S) or with only inactive lipid phosphatase activity (G129E), suggesting an indirect, lipid phosphatase-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 60 publications
3
30
0
Order By: Relevance
“…Activation of GSK-3b promotes pro-apoptotic signaling [64]. On other hand, PTEN is a negative regulator of PI3K signaling and alters tau phosphorylation in cells by mechanisms independent of GSK-3b [65]. Our results show that both Ab1-42 and Ab25-35 peptides induce neither Akt phosphorylation nor PTEN phosphorylation after 48 h of exposure.…”
Section: Discussionmentioning
confidence: 62%
“…Activation of GSK-3b promotes pro-apoptotic signaling [64]. On other hand, PTEN is a negative regulator of PI3K signaling and alters tau phosphorylation in cells by mechanisms independent of GSK-3b [65]. Our results show that both Ab1-42 and Ab25-35 peptides induce neither Akt phosphorylation nor PTEN phosphorylation after 48 h of exposure.…”
Section: Discussionmentioning
confidence: 62%
“…In accordance with these data, in vitro studies showed that over expression of wildtype PTEN reduces tau phosphorylation and aggregation indicating that PTEN protects against tau induced neurodegeneration [56,79]. Other studies failed to replicate these findings, and in contrast, reductions in the phosphorylated PTEN (inactive form) was found in some AD brains [80].…”
Section: Translational Neurosciencesupporting
confidence: 44%
“…This suggests that an increase in GSK3 activity or loss of negative regulation of GSK3 is insufficient to increase CRMP2 phosphorylation (Table 3). Similarly, phosphorylation of tau does not increase in concert with GSK3 activity [59,60]. Therefore, priming of CRMP2 by Cdk5 at Ser522 (and potentially tau at an unidentified site), prior to GSK3 phosphorylation, is a limiting factor.…”
Section: Gsk-3 and Cdk5mentioning
confidence: 94%